Adolf Hitler : Monologe im Führerhauptquartier 1941-1944 - Heims, Heinrich; Jochmann, Werner; Hitler, Adolf (München : Wilhelm Heyne, 1980)
Bibliotheek François Vercammen
Duits
Monografie
Keywords: Hitler, Adolf; Tweede Wereldoorlog; Berlijn